Drug discovery strategies for modulating oxidative stress in gastrointestinal disorders. (1st November 2020) - Mousavi, Taraneh; Hadizadeh, Nastaran; Nikfar, Shekoufeh; Abdollahi, Mohammad
ABSTRACT: Introduction: Due to the ever-growing incidence of gastrointestinal disorders accompanied by substantial economic impact, it is of great importance to manage these conditions globally. Since the significant role of oxidative stress has been proved in the initiation and propagation of most of the gastrointestinal disorders, medical science is now moving toward fusing traditional knowledge with advanced technology, aiming to promote the use of antioxidants in gastrointestinal disorders. Areas covered: Through PubMed, the Cochrane library, the WHO, Clinicaltrials.gov and Google Scholar, the US FDA, and EMA, the authors collated and reviewed the appropriate literature published between the 1 January 2015 and 31 March 2020 and provided their expert perspectives on the drug discovery strategies for modulating oxidative stress in gastrointestinal disorders. Expert opinion: As with other pharmaceuticals, antioxidants have been generally developed following the basic principles of drug discovery; the recent focus of which is designing multi-potent natural antioxidants mainly through using rational design and target-based drug discovery strategies. Although there have been encouraging in-vivo studies on the use of antioxidants in gastrointestinal disorders, especially inflammatory bowel disease and gastritis, there have been considerable deficits regarding in-vitro and clinical applications that should be immediately addressed.